1871 Tex. Gen. Laws ch. 34, §1 - (:unkn) unknown (My University, 1871)
Prohibited the carrying of any concealed pistol, dirk, dagger, slungshot, sword cane, spear, brass knuckles, Bowie knife, or any other kind of knife used for offense or defense, unless carried openly for self-defense. Punishable by fine of up to twenty-five but not more than one hundred dollars, forfeiture of the weapon, and for subsequent offenses, imprisonment up to 60 days.
Keywords: CARRY - CONCEALED